WVibes a wireless vibration-based earthquake sensing system - Balanay, Jose Mari S. (2011)
Wireless sensor networks (WSN) are currently implemented and utilized for Structural Health Monitoring (SHM) of civil structures to offset the high installation cost and complexity of wired systems. The WSN for this application is usually composed of wireless sensor nodes deployed over vital points of a structure. The nodes monitor the structure continuously over time and provide critical and reliable information that is wirelessly sent to a central base station. Routing protocols, such as the multi-hop protocol, extend the wireless communication range of a node for wider coverage of large infrastractures. Other protocols update the system model of the network for better reliability during node failure occurences. Vibration monitoring is one approach used for SHM and to make it more effective, placement of the sensors to the vital points of a structure is necessary. Current wireless vibration monitoring devices are limited on their capabilities, especially if a sensor network is desired, and are often expensive. For a developing country like the Philippines, it would be wiser to invest on a cost-effective and customizable sensor network that adapats based on the size and topology of a structure that will be monitored. The research project is a WSN vibration-based earthquake monitoring system that is composed of six slave sensor nodes and a base station node. The slave sensor nodes are mote platforms equipped with a tri-axial accelerometer to measure vibrations and a radio chip for wireless data transmission. Data measured by the slave nodes are transmitted wirelessly until it reaches the base station node, which acts asa the data sink, and is responsible for the serial interface of the (base station) PC to the sensor network. The base station node is also responsible for time synchronization of the system. Lastly, the base station (PC) handles the logging and storage of data for future processing and analysis. The project verified the feasibility of using the MICAz mote and a custom-made vibration sensor board for sensing and measuring earthquakes and also for monitoring structures.